PENGARUH PEMBERIAN ASAM LAURAT TERHADAP APOPTOSIS SEL HELA SECARA IN-VITRO - PRANATA EFFENDI, DIDIT Pranata (Universitas Negeri Surabaya, 2012)
Cervical cancer is the most woman cancer in the world. It caused by Human Papilloma Virus (HPV) which can inactivate some genes that have crucial role on cell cycle and apoptosis. Some cancer treatment such as surgery, chemotherapy and radiotherapy are proved ineffectively. We observed potentially of lauric acid as cancer herbal therapy. Lauric acid has anti free radical activity that important for cancer treatment. This study aim is to observe about the effect of laurid acid on HeLa cell apoptosis and expression of caspase 9 by using in-vitro. The apoptosis of HeLa cell is analyzed by caspase 9 protease enzyme absences by using immunocytochemistry with primary antibody anti caspase 9 and secondary antibody anti rabbit biotin. Percent apoptosis is measured by ratio between numbers of caspase 9 expression HeLa cell and total HeLa cell number times by 100%. The number of cell is counted by microscopy observation using difference color of cell on 5 areas. The brown color show the caspase 9 expression HeLa cell and violet color show the live HeLa cell. The result show that 0,0125 µl/ml of lauric acid giving posses highest caspase 9 expression and percent apoptosis on HeLa cell in-vitro.The apoptosis of HeLa cell is increase along with increasing of lauric acid concentration.